Pemanfaatan Penyaluran Alokasi Dana Desa Rintis Kecamatan Silangkitang Kabupaten Labuhanbatu SelatanTahun 2019-2021 - Tri Kurniati; Sri Sudiarti; Laylan Syafina (Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study was to find out the use of the village fund allocation budget in 2019 before the pandemic and in 2020-2021 during the Covid-19 pandemic in Rintis Village, Silangkitang District, South Labuhanbatu Regency. This research is a qualitative descriptive study. The subjects of this study amounted to 7 people including the Village Head, Village Secretary, Village Head and the community. This study uses qualitative data types with primary and secondary data sources and data collection techniques are observation, interviews and documentation. The data analysis technique uses data reduction, data presentation and verification. The results showed that Rintis Village, Silangkitang District, Labuhanbatu Selatan Regency used the village fund budget in accordance with applicable laws and regulations. The process of budget management or planning is carried out by means of planning, implementation, administration, reporting and accountability. In 2019 before the pandemic, village funds were used for village development and other community development, while in 2020-2021 during the COVID-19 pandemic, village funds were used to handle COVID-19 prevention and Village Cash Direct Assistance in accordance with the Village Minister Regulation regarding priority use. village funds in 2020 and 2021.